Pengaruh Faktor Fundamental, Pengungkapan Risk Management, dan Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan - Lestari, Andi Chandra Purnama; Nohong, Mursalim; Pakki, Erlina (YUME : Journal of Management, 2023)
This study aims to examine the influence of Fundamental Factors including Current Ratio, Total Debt to Total Assets, Net Profit Margin, and Fixed Assets Turnover Ratio, as well as Risk Management Disclosure, and Corporate Social Responsibility (CSR) on the Value of Manufacturing Companies on the IDX. This study took samples on manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021 with the use of an annual period. The data of this study uses secondary data, namely a continuous annual report for the last 3 years using meode purposive sampling. The analysis method of this study is by Descriptive Statistical Test, Classical Assumption Test, Multiple Regression Equation Model and Hypothesis Test.Keywords: Fundamental Factors, Current Ratio, Total Debt to Total Assets, Net Profit Margin, Fixed Assets Turnover Ratio, Risk Management Disclosure, Corporate Social Responsibility (CSR)